Study on the effect of cementation solution concentration on sand fixation by fiber reinforced MICP - Huan Tao; Chaochao Sun; Jili Qu; Yuandong Huang (PLoS ONE, 2025)
This study systematically investigates the influence of cementation solution concentration on the sand fixation effect induced by palm fiber-enhanced microorganisms through microbial induced calcium carbonate precipitation (MICP), aiming to optimize its application in ecological restoration and engineering reinforcement. A series of experiments including unconfined compressive strength tests, direct shear tests, permeability tests, nuclear magnetic resonance analysis, calcium carbonate content determination, scanning electron microscopy (SEM), and X-ray diffraction (XRD) evaluates the mechanical properties, permeability, and microstructural characteristics of MICP-treated sand under varying cementation concentrations ranging from 0.2 to 0.7 mol/L. Results show that a concentration of 0.5 mol/L yields the best mechanical performance, with significantly higher unconfined compressive strength (666.65 kPa) and shear strength compared to other concentrations. At lower concentrations from 0.2 to 0.4 mol/L, increasing the concentration enhances calcium carbonate deposition, which improves mechanical properties and reduces both permeability coefficient and porosity. In contrast, higher concentrations above 0.5 mol/L inhibit microbial enzymatic activity, leading to reduced calcium carbonate content and mechanical strength, along with increased permeability and porosity. Microscopic analysis reveals that at 0.5 mol/L, calcium carbonate crystals form densely and uniformly, effectively filling pore spaces and strengthening inter-particle bonding. Therefore, 0.5 mol/L represents an optimal balance between performance and cost, reducing resource waste while ensuring mechanical enhancement and supporting applications in sand dune stabilization, windbreaks, sand fixation, and ecological vegetation restoration.